Evaluation of BioFoam for Anastomotic Bleeding in Cardiovascular Surgery - Alfieri, Ottavio (AORTA, 2018)
Background Hemostatic agents are increasingly used as an adjunct to standard methods of controlling anastomotic bleeding in surgical procedures. The purpose of this study was to investigate the safety and effectiveness of BioFoam Surgical Matrix used as an adjunct for anastomotic hemostasis following cardiovascular surgery.Methods A prospective, multicenter, single arm study was conducted with 75 subjects treated with BioFoam following a total of 105 elective cardiovascular surgical procedures. Time to hemostasis was recorded following a single application of BioFoam in 74 subjects. Safety evaluations included intraoperative administration of a blood product, requirement for alternative means to achieve hemostasis, and the incidence of reoperation for bleeding.Results Hemostasis within 3 minutes was achieved in 62 (84%) of the 74 subjects and within 10 minutes in 69 (93%) of these subjects. BioFoam was well tolerated. Twelve (16%) of the 75 enrolled subjects each experienced one adverse event, and 13 serious adverse events were reported in 10 (13.3%) of the subjects. None of the adverse events was considered by the Investigators to be related to BioFoam. Blood products were administered to 14 (18.6%) of the 75 subjects, banked autologous blood was given to 5 (6.6%) subjects, and 57 (75.7%) subjects required only a cell saver. Four (5.3%) of the 75 subjects required reoperation for bleeding within 24 hours of surgery. There were no observations of bleeding in any subject at discharge and no reoperation for bleeding following discharge. The mean operation time was 218.2 (±72.2) minutes.Conclusions This study demonstrates the effectiveness of BioFoam Surgical Matrix when used as an adjunct for anastomotic hemostasis following a broad range of cardiovascular surgical procedures. The safety outcomes were within the normal limits for the types of procedures performed.
Keywords: BioFoam; hemostatic agent; surgical sealant; cardiovascular surgery